DESAIN SISTEM INFORMASI AKUNTANSI PERSEDIAAN PADA PD. FAJAR RAYA - B51109053, Afrianto (Jurnal Kajian Ilmiah Akuntansi Fakultas Ekonomi UNTAN (KIAFE), 2013)
Accounting Information Systems ( AIS ) is a collection of the activities of the organization that is responsible for providing financial information and information obtained from transaction data for purposes of internal reporting to managers for use in planning and controlling current and future operations and external reporting to shareholders , government and other outside parties . Problem in PD . Fajar Raya is the absence of information systems for inventory control inventory stock available . Therefore , in this paper the authors tried to design an information system inventory accounting . Author of the research methods used in the manufacture of paper is a description of research with direct observation through interviews and questionnaire administration . With these studies , will ultimately provide output in the form of inventory accounting information system design is suitable for PD . Fajar Raya . Where the design of the system can provide the required information about the inventory . Keywords : Inventory , Accounting Information Systems